Apology Strategies Used by the Ninth Grade Students of MTs Almahfudz in the Academic Year of 2024/2025 - Ashari, Yunika Fajar; Johan, Andrian Nuriza; Nugraeni, Ismawati Ike (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study describes the apology strategies employed by ninth-grade students at MTs Almahfudz in the academic year of 2024/2025. Apologies are a crucial component of pragmatic competence in English as a Foreign Language (EFL), yet their use among junior high school students remains underexplored. Every student has their own unique way of apologizing and the way to express apology is unique to be analyzed. Using a descriptive qualitative approach, data were gathered through a Discourse Completion Test (DCT) by Harb 2015. The analysis followed the framework developed by Olshtain and Cohen’s (1983), which classifies apology strategies into five categories: Illocutionary Force Indicating Device (IFID), acknowledgment of responsibility, explanation of account, offer of repair, and promise of forbearance. Results reveal that IFID was the most frequently employed strategy (34.6%), followed by acknowledgment of responsibility (24.3%), explanation of account (20.3%), offer of repair (11.7%), and promise of forbearance (9.1%). The study also found that students often combined multiple strategies to strengthen their apologies. Future research could explore how social variables such as gender and age impact the choice of apology strategies.